The performance evaluation of the open-end equity mutual fund in China - Shi, Chen (2018)
The fund industry has made a great progress in China. However, as one of the main kinds of fund, the performance of equity mutual fund is not good. Especially in these few years, the Chinese stock market transform from a bull market to a bear market. Investors have suffered losses and they begin to doubt about the performance of equity mutual fund. Thus, it is urgent to accurately evaluate the return of equity mutual fund in the Chinese market.